City Size, Pollution and Emission Policies - Michael P. Pflüger (Institute of Labor Economics (IZA), 2018)
This paper develops a micro-founded city systems model with an endogenous number of cities to explore whether local governments establish the optimal city size when production processes involve environmental pollution. Our analysis delivers two key insights. First, if an optimal scheme to regulate environmental pollution is implemented, cities chosen by local governments are never too large. They are too small if pollution is purely global, but at the optimal size, if pollution is purely local. Second, if no emission scheme is implemented or if emission policies are too lax, then cities steered by local governments, become too large, however.
Keywords: H73; R12; Q50; 330; city systems; environmental pollution; emission policies